2021
DOI: 10.1002/ehf2.12739
|View full text |Cite
|
Sign up to set email alerts
|

One year prognostic value of B‐lines in dyspnoeic patients

Abstract: Aims Studies have demonstrated the reliability of B-lines evaluated by lung ultrasonography to identify pulmonary congestion, but information is lacking about its utility as a prognostic marker of heart failure (HF). We sought to assess the prognostic midterm value of B-lines in ambulatory patients presenting with dyspnoea, as an additive tool for patient management and to avoid acute HF exacerbations. Methods and results A total of 93 patients presenting with dyspnoea (New York Heart Association ≥2) were pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
(62 reference statements)
1
8
0
Order By: Relevance
“…The feasibility of the LASr measurements was 92%. During the 26 [22,32] months follow up we detected 11 events: 4 patients were treated at an emergency department for an acute HF episode, 2 patients were admitted to the cardiology ward due to severe HF symptoms, 3 patients needed ambulatory intensification of loop diuretic treatment due to worsening of HF symptoms and 2 patients died (1 unknown cause, 1 patient during HF event). Having >15 B-lines significantly increased the risk of the endpoint events, and during the multivariate analysis, proved it to be an independent predictor of endpoint events (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility of the LASr measurements was 92%. During the 26 [22,32] months follow up we detected 11 events: 4 patients were treated at an emergency department for an acute HF episode, 2 patients were admitted to the cardiology ward due to severe HF symptoms, 3 patients needed ambulatory intensification of loop diuretic treatment due to worsening of HF symptoms and 2 patients died (1 unknown cause, 1 patient during HF event). Having >15 B-lines significantly increased the risk of the endpoint events, and during the multivariate analysis, proved it to be an independent predictor of endpoint events (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…B-lines also have an exceptional prognostic value, shown in patients with HF (19)(20)(21)(29)(30)(31). After a 1-year follow-up in dyspneic patients, an increased number of B-lines was associated with a higher hospitalization rate with a best cut-off at 6 B-lines (8 sector LUS) (32). Measurement of PC at discharge provides prognostic information for patients with either HFpEF (33,34) or HFrEF (34).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that residual pulmonary congestion by LUS predicts adverse events in chronic HF. 21 However, a standardized definition for residual pulmonary congestion is not established yet. Previous authors have reported several cut-off numbers of B-lines with prognostic significance according to the LUS protocol performed and the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have reported several cut-off numbers of B-lines with prognostic significance according to the LUS protocol performed and the clinical setting. 21 , 22 In many cases, they employed the area under the ROC curve to identify the best number to predict the adverse outcomes by applying the Youden criteria. In our study, as residual pulmonary congestion develops when LAP increases beyond a critical threshold, we employed the area under the ROC curve to identify the best number to predict above a pivot point of the increasing number of B-lines.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, indications for LUS are growing in cardiology, especially in patients with heart failure or dyspnea ( 5 , 6 ). LUS can predict the prognosis of patients with acute and chronic heart failure ( 7 , 8 ), and LUS-guided treatment can reduce the rehospitalization rate of patients with HF ( 9 ).…”
Section: Introductionmentioning
confidence: 99%